The Changes in Color of Pineapple Stem Extract (Ananas comosus (L.) Merr) with Carbamide Peroxide as a Dental Bleach toward Dental Surface Violence in Vitro - Deli Mona; Laura Ajeng Dyalova (Faculty of Medicine, Universitas Andalas, 2022)
Objective: The purpose of this research was to determine the effectiveness comparison of pineapple stem extract (Ananas comosus (L.) Merr) and carbamide peroxide home bleaching for tooth whitening agent. Methods: The method of this research was in vitro experimental laboratory. The sample was 28 post-extracted premolar teeth divided into 4 groups (50%, 75%, and 100% concentration of pineapple stem extract) and control soaked in carbamide peroxide 10%. The measurement of color changes was observed with shade guide Vitapan Classical. This study used Kruskal Wallis test for data analysis (p<0.05). Results: This research showed that the mean of tooth color difference respectively for 50%, 75%, 100% concentration of pineapple stem extract and carbamide peroxide 10% were 8.14, 10.14, 12,00 and 9.14. The highest mean was pineapple stem extract 100% and the lowest mean was pineapple stem extract 50%. Conclusion: The conclusion of this study was pineapple stem extract 100% was more effective than 50%, 75% concentration of pineapple stem extract and carbamide peroxide 10%. Keywords: Pineapple stem extract, Carbamide peroxide, Tooth whitening